PERSPECTIVES OF LIBRARIANS ON THE IMPACT OF CYBER THREATS IN THE MANAGEMENT OF DIGITAL LIBRARIES IN KWARA STATE, NIGERIA - Ibraheem, Idris; Yusuf, Abdullahi Adebola; Aremu, Bolakale Lawal; Jidda, Muhammad Tijjani (FUDMA JOURNAL OF SCIENCES, 2025)
This study examines the perspectives of librarians on the impact of cyber threats in managing digital libraries in Nigeria within the context of the Fifth Industrial Revolution. As digital libraries expand, they face growing risks such as data breaches, ransomware, and phishing, which threaten their integrity and accessibility. Data was collected through surveys administered to digital library professionals and analyzed using Python-based tools, including descriptive statistics, comparative tests, and a Random Forest model. The analysis revealed that cyber threats are perceived as more disruptive in public libraries than in academic ones. Public libraries prioritize data encryption, while academic libraries emphasize access control and regular software updates. Confidence in managing cyber threats varies with experience, as less experienced staff report high confidence but moderate familiarity. The Random Forest model achieved 95% accuracy, confirming that experience, library type, and security measures predict threat exposure. The findings emphasize the need for continuous cybersecurity training and tailored defense strategies to enhance digital library resilience in Nigeria.